What's wrong with the back of the envelope? A call for simple (and timely) benefit–cost analysis. Issue 2 (26th April 2016) - Carrigan, Christopher; Shapiro, Stuart
Abstract: Observers across the ideological spectrum have criticized benefit–cost analysis for as long as it has been part of the rulemaking process. Still, proponents and detractors agree that analysis has morphed into a mechanism often used by agencies to justify regulatory decisions already made. We argue that a simpler analysis of more alternatives conducted earlier in the regulatory process can resuscitate it as a tool to inform policy. Recognizing that requiring a procedure does not ensure that regulators will follow it, we offer possible remedies, including strengthening or relaxing subsequent review of proposed rules, which raise the cost of circumventing the reform or lower the cost of following it.